“Rendimiento y características diferenciadas de seis accesiones del cultivo de chuin (pachyrhizus tuberosus L.) en morales, tarapoto San Martín” - Grandez Pezo, Luis (2003)
The present project has main objectives: first, to evaluate the performance of the tuberous root which is a product of six cultivations of "chuin" (Pachyrhizus tuberosus), in Morales, San Martín, PERU, and, in second place, identify the most important characteristics in other to classify the varieties of "chuin". This cultivations were located in the "Oasis" farm, which is run by the National University of San Martin - Tarapoto - PERU. You can have access to this farm by 'Fernando Belaunde Terry' road (Marginal Norte) Tarapoto - Moyobamba, turning left where the Bridge over the Cumbaza river is. We used the 'block design', following no pattern, with 6 treatments, and 4 repetitions. We made to evaluations and we get to the following conclusions: we had a better performance (t/hectares), 64,8 t/Hectares, of the tuberous root with the treatment T1 (TC 504). The 6,7 cm. root diameter obtained with the treatment TS (TC557). With the treatment T3 (TC549) we obtained 25,3 cm root diameter. And, the most appropriate for the varieties (accessions) are TC504, TC549, TC558 which had a good performance without showing difference from the point o view statistics records.